2003
DOI: 10.1094/pdis.2003.87.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of Paenibacillus lentimorbus to Botryosphaeria dothidea and Biological Control of Panicle and Shoot Blight of Pistachio

Abstract: A potential microbial fungicide, Paenibacillus lentimorbus isolate CBCA-2, against Botryosphaeria dothidea, the pistachio panicle and shoot blight fungus, was obtained from healthy pistachio leaves by both in vitro and in vivo screening techniques. CBCA-2 caused 100% inhibition of pycnidiospore germination after 24 h incubation at 25°C. Malformation of pycnidiospores and hyphae, and lysis and swollen pycnidiospores of B. dothidea occurred in the presence of cell suspensions of CBCA-2. Among the five media test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…AF499610). Several bacterial isolates reported to be P. lentimorbus, based on fatty-acid analysis, are likely misidentified (Chen et al, 2003;Montealagre et al, 2003;DasGupta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…AF499610). Several bacterial isolates reported to be P. lentimorbus, based on fatty-acid analysis, are likely misidentified (Chen et al, 2003;Montealagre et al, 2003;DasGupta et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Though the antibiotic-producing potential of Bacillus and Paenibacillus species has been recognized for more than six decades, very few reports are available on the antifungal trait of P. lentimorbus (Chen et al 2003;Dasgupta et al 2006). Recently, Nautiyal et al (2006) reported that P. lentimorbus B-30488, isolated from the milk of Sahiwal cows showed antifungal activity against Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Similar biocontrol effectiveness of antagonistic bacteria against Botryosphaeria spp. has also been reported in panicle and shoot blight of pistachio (Chen et al., ) and apple ring rot (Chen, Zhang, Fu, Li, & Wang, ).…”
Section: Discussionmentioning
confidence: 61%
“…Similar biocontrol effectiveness of antagonistic bacteria against Botryosphaeria spp. has also been reported in panicle and shoot blight of pistachio (Chen et al, 2003) and apple ring rot (Chen, Zhang, Fu, Li, & Wang, 2016). thaliana (Timmusk & Wagner, 1999) and cucumber (Benhamou, Gagne, Quere, & Dehbi, 2000;Chen et al, 2000).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation